Pembangunan jadual input-output wilayah dan analisis ke atas struktur industri Selangor - Saari, Mohd Yusof; Abdul Rashid, Zakariah (Universiti Utara Malaysia, 2009)
Purpose – This paper attempts to estimate a regional input-output table for Selangor for 2000. Then, the regional input-output table is used to analyse the production structures in Selangor. Design/Methodology/Approach – The regional input-output table for Selangor is estimated by applying the RAS technique. Accordingly, under the homogeneity assumption of production structures and technologies between Selangor and Malaysia, the structure of Selangor’s inter-industry is estimated based on the structure of national inter-industry transactions. Findings – Results showed that Selangor has modest production structure and highly dependent on imports and exports. The inter-industry linkages analysis indicated that manufacturing, mining and quarrying, and government service sectors are the key sectors in Selangor, where these sectors have potential to stimulate growth in the economy.Originality/Value – This paper is a pioneer study for the construction of a regional input-output table for Malaysia, especially for Selangor, by using a partial survey approach. For the purpose of planning, the regional input-output table is an important economic tool because it compiles the whole demand and supply of production sectors in an economy.Paper type – Research paper